1963
DOI: 10.2134/agronj1963.00021962005500060015x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Population Levels on Yield and Maturity of Maize Hybrids Grown on the Northern Great Plains1

Abstract: Synopsis Plant production reached a maximum at 12,000 to 16,000 plants per acre in eastern South Dakota. Grain production reached a maximum at the same level and fell off drastically if population levels exceeded this optimum. Under conditions of drouth, maximum yields may be associated with very low population levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

1971
1971
1993
1993

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 7 publications
2
13
0
Order By: Relevance
“…Table 4a showed that N application significantly influenced number of cobs at NIFOR, Uyo and Mokwa. The highest yield ought to have been recorded at the highest plant density, but the cob size decreased as population increased, which agrees with other results [16]. This confirms the fact that the number of cobs is directly related to yield.…”
Section: Resultssupporting
confidence: 91%
“…Table 4a showed that N application significantly influenced number of cobs at NIFOR, Uyo and Mokwa. The highest yield ought to have been recorded at the highest plant density, but the cob size decreased as population increased, which agrees with other results [16]. This confirms the fact that the number of cobs is directly related to yield.…”
Section: Resultssupporting
confidence: 91%
“…Many workers have shown lodging to increase at higher densities (Zuber et al, 1960;Termunde et al, 1963;Rutger and Crowder, 1967), and these results are consistent with results of my study. Percentage lodging was increased by stress imposed by high plant densities, but planting date had no effect on lodging (Table 21).…”
Section: Harvest Indexsupporting
confidence: 92%
“…In several studies, percentage lodging was increased and stalk diameters were decreased as plant densities were increased (Zuber et al, 1960;Termunde et al, 1963;Rutger and Crowder, 1967). Allison (1969) showed that stem weight began to decrease in denser plantings three to four weeks after flowering.…”
Section: Density Tolerancementioning
confidence: 99%
“…Confounding the results of the Georgia data are the different population densities for the two types of trials. Hybrid X population-density interactions have been reported to be significant in several studies (Colville et al, 1964;Duncan, 1954;Lang et al, 1956;Rutger and Crowder, 1967;Termunde et al, 1963). Most of the interactions have been associated with maturity differences.…”
Section: Results and Discussion Cornmentioning
confidence: 95%